2013
DOI: 10.1002/14651858.mr000032.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve retention in randomised trials

Abstract: BackgroundLoss to follow-up from randomised trials can introduce bias and reduce study power, affecting the generalisability, validity and reliability of results. Many strategies are used to reduce loss to follow-up and improve retention but few have been formally evaluated.ObjectivesTo quantify the effect of strategies to improve retention on the proportion of participants retained in randomised trials and to investigate if the effect varied by trial strategy and trial setting.Search methodsWe searched the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
244
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(251 citation statements)
references
References 118 publications
(336 reference statements)
7
244
0
Order By: Relevance
“…We searched the recent Cochrane systematic review of interventions to reduce trial attrition for embedded trials of enclosing a pen with a questionnaire mailing and found a single study by Sharp and colleagues (described previously [10]). We combined the results of this study with ours in a fixed effects meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We searched the recent Cochrane systematic review of interventions to reduce trial attrition for embedded trials of enclosing a pen with a questionnaire mailing and found a single study by Sharp and colleagues (described previously [10]). We combined the results of this study with ours in a fixed effects meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%
“…There have been a number of systematic reviews appraising the literature surrounding non-monetary incentives to increase response rates [3,7,10]. Together, these have identified five trials evaluating the effect of adding a pen or pencil to postal mail outs on response rate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not address other methods that could be used to mitigate loss to follow-up, such as monetary incentives, which have been previously shown to improve response rates. 7 However, the use of monetary incentives carries both practical and ethical considerations, particularly in the context of a clinical trial. Given that email has also been effective at decreasing study attrition for postal questionnaires, email may be another effective, low-cost option to use going forward.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Despite the widespread application of text messaging to facilitate health care delivery, there is a paucity in the literature supporting the use of text messaging to facilitate clinical research, specifically to assist in research participant follow-up. 7 Incomplete or missing outcome data from patients lost to follow-up or patients who withdraw from study participation present a major threat to the internal and external validity of a clinical trial. The study results may be biased if patients are unable to follow up because of factors related to the outcome of interest.…”
Section: Introductionmentioning
confidence: 99%